A STANDARD MASS MEDIA IMAGE ANALYSIS - Ștefan VLĂDUȚESCU (Annals of the University of Craiova for Journalism, Communication and Management, 2018)
This research aims to clarify the joints and structure of a standard media image analysis. It is argued a) that the image is a symbolic footprint; b) that the subject of the image is a person, an organization (group, enterprise, people, nation), institution or product, and c) that the image appears, is being built, deconstructed and can be shed from communication processes. The steps of a standard media image analysis and the information tiles that are used within it are specified. Finally, a case study illustrates practically how such an analysis is carried out.